Cognitive impairment, depressive and anxiety disorders among post-COVID-19 survivors: a follow-up study - Ayman A. Aziz; Ahmed A. Latif; Sandra W. Elseesy (Middle East Current Psychiatry)
Abstract Background Psychiatric signs may be induced by the cytokine storm that is implicated in the immune response to coronavirus through neuro-inflammation. Survivors disclosed symptoms of obsessive–compulsive disorder, melancholy, anxiety, panic disorder, and post-traumatic stress disorder. For the first year following the SARS disease, they generally suffer from suicide and psychosis. Aim To evaluate the presence of cognitive impairment, anxiety disorders, and depression in adult survivors of COVID-19, 1 month and 3 months post-recovery. Method It is an observational longitudinal study. Forty-four COVID-19 survivor patients, with no past psychiatric history were evaluated at 3 months and 1 month after recovery. The Montreal Cognitive Impairment Basic (MoCA-B) was employed to evaluate cognitive impairment. However, anxiety and depressive disorders were identified via structured clinical interview for DSM IV, axis I (SCID-I) and their severity was examined by the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) consecutively. Results Regarding cognitive impairment, MoCA-B results showed a mean score of 25.95 ± 1.98 in the 1st interview and 27.7 ± 1.05 in the 2nd interview, with a marked change, P-value = 0.001. SCID-I showed that 43.2% of our sample was diagnosed with both anxiety and depression at 1 month post-recovery, with the improvement of some cases at 3 months to affect only 18.2%, showing a statistically significant difference, P-value = 0.036. The percentage of patients who suffered from sleep difficulties was 59.1% at 1st interview and 27.3% at 2nd interview. While 61.4% of patients suffered from fatigue and low concentration at 1st interview and went down to 31.8% at 2nd interview, showing a statistically significant difference, P-value < 0.001. The severity of depression and anxiety in those diagnosed also declined from the 1st interview to the 2nd, BDI mean score in 1st interview was 12.30 ± 10.46, and in the 2nd interview was 7.09 ± 9.24 with marked variation P-value < 0.001, while BAI means score at the 1st interview was 18.18 ± 16.85 and at the 2nd interview was 11.32 ± 16.12 with statistically significant difference P = 0.001. Conclusion Impairment of cognitive functions; especially delayed recall; was one of the important COVID-19 psychiatric sequelae, In addition to anxiety and depressive signs in the form of depressed/anxious mood, fatigue, decreased concentration, and sleep disturbances. The severity of symptoms declined over the 3 months period of the study.